2018
DOI: 10.1007/s00784-018-2483-1
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT evaluation of different final irrigation protocols on the removal of hard-tissue debris from isthmus-containing mesial root of mandibular molars

Abstract: This study highlighted that all final irrigation protocols (PUI, EndoVac, SAF, and EasyClean) promoted a similar removal of AHTD. However, none of the final irrigation protocols was able to render mesial canals of mandibular molars completely free from packed debris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 37 publications
4
58
0
6
Order By: Relevance
“…, Silva et al . ), none of the tested irrigation protocols was able to render the isthmus of mesial root canal systems of mandibular molars completely free of debris. In the present study, no significant differences were observed between final irrigation protocols regarding the removal of AHTD.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…, Silva et al . ), none of the tested irrigation protocols was able to render the isthmus of mesial root canal systems of mandibular molars completely free of debris. In the present study, no significant differences were observed between final irrigation protocols regarding the removal of AHTD.…”
Section: Discussionmentioning
confidence: 91%
“…, Silva et al . ) and has been proved to be a precise tool for quantitative and qualitative evaluation of hard‐tissue debris within the root canal system (Paqué et al . , De‐Deus et al .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the limitations of conventional irrigation, several irrigation activation techniques such as sonic, ultrasonic devices, lasers and negative pressure irrigation system have been employed to improve the efficacy of cleaning and debriding solutions (Gu et al , Gutmann & Lovdahl ). Recent studies have investigated the efficacy of these techniques in removing AHTD from isthmus‐containing mesial root canals of mandibular molars (De‐Deus et al , Freire et al , Keleş et al , Versiani et al , Leoni et al , Verstraeten et al , Passalidou et al , Silva et al ). Ultrasonically activated irrigation (UAI) is apparently the predominant agitation technique in clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium hypochlorite (NaOCl) is the most commonly used root canal irrigant; it has an effective antimicrobial activity, a broad bacterial range, and creates a significant reduction in endotoxins levels (Zehnder , Fidalgo et al , Neelakantan et al ). However, several studies have demonstrated that complete bacterial elimination cannot be achieved consistently with any of the current disinfection protocols (Siqueira Jr et al , Silva et al ). Therefore, efforts have been made to develop novel techniques to provide additional disinfection for the root canal system, such as passive ultrasonic irrigation (PUI) (Dioguardi et al ), photodynamic therapy (PDT) (Eslami ), continuous irrigating techniques (Dioguardi et al , Silva et al ) and apical positive and negative pressure irrigation methods (Dioguardi et al , Eslami , Silva et al ).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have demonstrated that complete bacterial elimination cannot be achieved consistently with any of the current disinfection protocols (Siqueira Jr et al , Silva et al ). Therefore, efforts have been made to develop novel techniques to provide additional disinfection for the root canal system, such as passive ultrasonic irrigation (PUI) (Dioguardi et al ), photodynamic therapy (PDT) (Eslami ), continuous irrigating techniques (Dioguardi et al , Silva et al ) and apical positive and negative pressure irrigation methods (Dioguardi et al , Eslami , Silva et al ). Amongst these protocols, ozone therapy has been investigated aiming to increase microbial load reduction within the canal system and thus improve endodontic outcomes.…”
Section: Introductionmentioning
confidence: 99%